Analysis of a New Approach in Higher Education - Toshnazarov Nurislam Bakhodirovich (Journal of Higher Education and Academic Advancement, 2024)
In this article, educational platforms that include the adaptive implementation of the educational process, which is possible through the use of SMART educational technologies, flexible interaction with the social, economic and technological environment in the implementation of the SMART education paradigm. It is aimed at forming the education and training process to acquire the knowledge, skills and abilities necessary for communication, and opinions and considerations were made about the possibility of using the global information society to meet the needs and interests of SMART education.